2012
DOI: 10.1177/0961203312446974
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid syndrome in northwest Italy (APS Piedmont Cohort): demographic features, risk factors, clinical and laboratory profile

Abstract: We report the experience from the Antiphospholipid Antibodies (aPL) Regional Consortium in northwest Italy, meant to support clinical research and foster collaboration among health professionals regarding the diagnosis and management of antiphospholipid syndrome (APS) patients. This cohort-study (APS Piedmont Cohort) was designed to register the clinical characteristics at inception and associated immunological manifestations at diagnosis (if any) of patients who strictly fulfilled the current criteria for APS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 8 publications
1
27
1
Order By: Relevance
“…It must be underlined that a great deal of these patients was under OAT, and the higher the INR intensity, the higher the recurrence rate. Thrombotic recurrences are generally higher (when calculated) in the first year of followup [9], [12], [18] and [21].…”
Section: Conclusion and Commentsmentioning
confidence: 95%
See 4 more Smart Citations
“…It must be underlined that a great deal of these patients was under OAT, and the higher the INR intensity, the higher the recurrence rate. Thrombotic recurrences are generally higher (when calculated) in the first year of followup [9], [12], [18] and [21].…”
Section: Conclusion and Commentsmentioning
confidence: 95%
“…Second, the possibility that a clinical subset of APS vascular exists, i.e., those who have recurrences despite correct OAT, must be seriously considered. This fact represents a treatment failure, and some studies have shown that this is not at all a rare event [9], [12] and [37]. In particular, this happens in higher risk patients for aPL profile (triple positivity, Miyakis types 1 and 2a) [38].…”
Section: Conclusion and Commentsmentioning
confidence: 99%
See 3 more Smart Citations